Union by Co-Lamination of Aluminum and Magnetic alloy obtained by Rapid Solidification (2022)
The aim of this work is to analyze the possibility of producing a joint by lamination of an Al-1050 plate and Fe78Si9B13(%at.) soft magnetic ribbons material obtained by a rapid solidification process by using the Melt Spinning (MS) technique. The lamination conditions are studied on the characteristics of the joint, the microstructure, and the magnetic properties. Mainly the surface preparation, temperature, and reduction of thickness. The material is characterized by X-Ray Diffraction, Optical, and Scanning Electron Microscopy, showing a completely amorphous structure before and after the collamination, the typical defects caused by this rapid solidification technique in ribbons (bubbles, dust particles, roughness imperfections and oxides) and the joint between materials. The microhardness Vickers has been determined in both, the ribbons as quenched and collaminated samples, to observe quantitatively the hardening suffered during colamination and find a possible cause. The Differential Scanning Calorimetry and Compositional Analysis by EDS techniques were also used to determine the crystallization temperatures and chemical exact chemical composition of the ribbons as received. The magnetic hysteresis curve of the amorphous ribbons showed a Hc and Ms around 3.8 A/m and 1.44 T correspondingly.